Gambaran Penggunaan Atibiotik Profilaksi Pada Pasien Seksio Cesarea di Rumah Sakit Umum Daerah KAB. Batang Periode Agustus-September 2022 - mitfah nirwani (Jurnal Adijaya Multidisplin, 2023)
In Permenkes no 72 year 2016 Prophylactic antibiotics are recommended in cesarean delivery because they can prevent or reduce the incidence of infections caused by germs during surgery. Cesarean delivery is an artificial delivery through the uterine wall to remove the fetus because spontaneous delivery cannot be performed. The number of sectio caesarean deliveries in Indonesia in 2013 was 9.8% (Ministry of Health, 2014). Sectio Caesarea (SC) is classified as clean contaminated surgery and based on research it is known that the administration of antibiotics can reduce the risk of endometritis by 60-70% and reduce the risk of surgical wound infection (ILO) by 30-65%. This study aims to determine the description of the use of prophylactic antibiotics in SC patients at RSUD Kab. Batang in the period August - September 2022. The research method used a retrospective descriptive design and data collection with total sampling technique. The number of samples studied and fulfilling the inclusion criteria were 74 patients. The results showed that every SC procedure was given prophylactic antibiotics, and showed that antibiotics used as prophylaxis in SC surgery were Cefazolin injection 1 gram (99%) and ceftriaxone 1 gram (1%) with administration time less than 15 minutes before incision (9%) and between 15 - 60 minutes before incision (91%). The conclusion of this study is that the use of prophylactic antibiotics in sectio caesarea patients at Batang District Hospital is in accordance with the Antimicrobial Stewardship Guidelines at Batang Regency Hospital in 2021. Keywords: Sectio Caesarea, Antibiotic Prophylaxis, ILO, Hospital